Mechanisms and Therapeutic Implications of ncRNAs in Regulating the PD-1/PD-L1 Axis Across Cancers - Jian, Huilin; Li, Xitai; Lei, Xiaoyong; Tang, Shengsong; Yang, Xiaoyan (Combinatorial Chemistry & High Throughput Screening, 2025)
Cancer remains one of the most challenging health issues worldwide. Thus, there is an urgent need to discover effective treatments for cancer. Immune checkpoint blockade targeting the PD-1/PD-L1 axis has revolutionized cancer therapy, yet resistance and limited clinical efficacy remain significant challenges. Emerging evidence highlights ncRNAs as upstream regulators of PD-1/PD-L1, offering novel therapeutic opportunities. This review systematically examines the role of miRNAs, lncRNAs, and circRNAs in modulating PD-1/PD-L1 signaling across diverse cancers, emphasizing their mechanisms and clinical implications. We further discuss the potential of ncRNAs as biomarkers and therapeutic targets to overcome immune evasion and enhance immunotherapy efficacy.
Keywords: long non-coding RNAs